2017
DOI: 10.3892/ol.2017.7648
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analyses associated with malignant phenotypes of metastatic sub-clones derived from a mouse oral squamous cell carcinoma Sq-1979 cell line

Abstract: Abstract. To elucidate the genetic events that occur during the development of OSCC, the present study established a model of oral malignancy using a mouse oral squamous cell carcinoma (OSCC) Sq-1979 cell line. Sq-1979 cells were implanted into syngeneic C3H mice. Subsequently, 233 cells and metastatic sub-clones (L cells) from primary OSCC, as well as the metastasized lymph node tissues of Sq-1979-implanted mice were established. Compared with parental Sq-1979 and 233 cells, the majority of L cells exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recent research demonstrated that the solute carrier (SLC) family of membrane transport proteins plays a role in modulating efferocytosis by upregulating the expression levels of anti-inflammatory genes and sustaining continuous efferocytosis [ 37 ]. It was reported that SLC16A13 could be a potential biomarker for tumor prognosis, including oral squamous cell carcinoma, lung adenocarcinoma, and pancreatic cancer [ 38 40 ]. However, the relationship between these two genes and GBM has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that the solute carrier (SLC) family of membrane transport proteins plays a role in modulating efferocytosis by upregulating the expression levels of anti-inflammatory genes and sustaining continuous efferocytosis [ 37 ]. It was reported that SLC16A13 could be a potential biomarker for tumor prognosis, including oral squamous cell carcinoma, lung adenocarcinoma, and pancreatic cancer [ 38 40 ]. However, the relationship between these two genes and GBM has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of syngeneic models is similar to the cell-derived xenograft (CDX) model. Several mouse cell lines can be used to develop syngeneic OSCC mouse models, including mouse OSCC Sq-1979 cells [ 36 ], mouse squamous cell carcinoma SCC7 [ 37 , 38 ], mouse oral cancer (MOC) cell lines [ 40 ], MOC1 [ 41 ], and MOC2 [ 42 ]. Moroishi et al [ 39 ] have demonstrated that transplanting SCC7 cells (1 × 10 5 ) into both hind flanks of C3H/HeOu mice resulted in aggressive tumor growth, whereas LATS1/2 dKO SCC7 cells did not result in tumors.…”
Section: Syngeneic Mouse Modelsmentioning
confidence: 99%
“…Nagaya et al [ 40 ] studied the effects of near-infrared photoimmunotherapy using syngeneic models developed through the subcutaneous injection of C57BL/6 mice with poorly immunogenic MOC2 mKate2 cells (1.5 × 10 5 ), moderately immunogenic MOC2-luc cells (1.5 × 10 5 ), and immunogenic MOC1 cells (2.0 × 10 6 ). Similarly, Adachi et al [ 36 ] injected Sq-1979 cells (1 × 10 7 ) into the posterior neck area of C3H/HeN mice to determine the genetic changes that occur throughout OSCC development. These studies demonstrate that different mouse OSCC cell lines could be successfully used to produce stable syngeneic OSCC models.…”
Section: Syngeneic Mouse Modelsmentioning
confidence: 99%
“…In order to compare the immune-modulatory effects of OSCCs in primary and advanced stages, we have established a metastasized model (L5-11cells) representing more malignant phenotypes than the parental OSCC (Sq-1979 cells) when implanted in the syngeneic mice [ 82 ]. Our results revealed that it is metastasized L5-11 cells, not early-stage Sq-1979 cells that predominantly induce PMN-MDSCs in tumor-bearing mice [ 83 ]; this is not simply reflecting the differential tumor size, since even the larger amount of inoculation of Sq1979 cells could not induce the MDSC cells in the mice.…”
Section: Myeloid-derived Suppressor Cells In the Tumor Microenvironmementioning
confidence: 99%